Arctic cinemas and the documentary ethos - Kaganovsky, Lilya; MacKenzie, Scott, 1967-; Stenport, Anna Westerståhl (Indiana University Press, 2019)
Arctic Cinemas and the Documentary Ethos is a comprehensive study of the creation of documentary cinema in and about the global Arctic region from Nanook of the North to the present day.